Ethnomedicinal and conservation evaluation of the traditional medicinal plant species employed by the Van Gujjar Tribe in the Dehradun Shivalik Hills, Uttarakhand, India - Gupta, Nishant; Agarwal, Ashok; Yadav, Virendra (Ethnobotany Research and Applications, 2023)
Background: To the best of our knowledge, this is the first quantitative and conservation ethnomedicinal evaluation of the Van Gujjar Tribe inhabited in the Delhi-Dehradun Highway Shivalik hills Belt (DHSB). The study area is situated adjacent to biodiversity hotspot Rajaji National Park, Uttarakhand, which is an important part of Himalayan systems. The area is ecologically sensitive, increasing anthropogenic disturbance and overexploitation of medicinal herbs is also major concern. So, along with conventional ethnobotanical studies, conservation analysis of the area is important. Methods: This ethnomedicinal study comprised extensive field surveys and repetitive interviews of 120 informants of the Van Gujjar tribe with different social and educational backgrounds. Procured data were analyzed using three different quantitative indices, i.e. the relative frequency of citations (RFC), informant consensus factor (ICF), and the fidelity level (FL%). Collected plant samples were identified by relevant flora literature and online plant databases. Identified species conservation status was derived from The IUCN online database. Results: A total of 71 medicinal plant species from 67 genera and 41 families were documented from the study area. The most frequently used species, Zingiber officinale Azadirachta indica A. Juss, and Ageratum conyzoides L. were employed for multiple health issues, mainly for digestive and respiratory disorders. The highest RFC values are Z. officinale (RFC = 1.0), A. indica A. Juss. (0.99) and A. conyzoides L. (0.92. FL% of these species were 96%, 90% and 83 % viz. The highest ICF value is 0.98, which shares dental & gum problems, digestive disorders and wounds categories. The IUCN status of 71 reported medicinal plant species indicated 28.1 % plant species were least concerned, 4.2 % critically endangered (Chlorophytum borivilianum,Commiphora wightii, Nardostachys jatamansi ), 1.4 % near threatened and 1.4 % endangered, 2.8 % Data Deficient, while 61.9 % species status remained unknown as currently not available in IUCN Red data list. Highly utilized species IUCN status however under ‘least concerned’ category. Conclusions: The study aids medicinal plant species data with current conservation status in the Delhi-Dehradun Highway Shivalik hills Belt. Medicinal plant species such as Chlorophytum borivilianum, Commiphora wightii, and Nardostachys jatamansi are critically endangered and others could be prone due to overexploitation. The present data could help to fill the previous conservation and quantitative ethnobotanical studies gaps in the study area. Keywords: Medicinal flora, Rajaji National Park, Himalaya, IUCN status, Critically Endangered Species, Traditional Knowledge,